Analysis of the value of multiculturalism in indonesian history textbooks in the independent curriculum - Santosa, Firdaus Hadi; Marta, Nuraeni; Humaidi, Humaidi (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2024)
This research aims to reveal the existence of multiculturalism values ​​in high school history textbooks in the Merdeka Curriculum. The method used in this research is a qualitative method with a content analysis approach, with the data source being high school history textbooks in the independent curriculum for classes X, XI, and XII. The research results show that (1) the value of multiculturalism in textbooks appears more often in factual material such as in classes XI and XII compared to conceptual material in class plurality. In contrast, the value of equality is mostly represented by a discussion of the role of women in Indonesian history. The conclusion is that there are quite a lot of multiculturalism values ​​contained in history textbooks in the Independent Curriculum, although teachers need to maximize them by adding more contextual examples to make the process of instilling multiculturalism values ​​easier.